SIMPLICITY OF ENGLISH LANGUAGE COMPARED TO OTHER LANGUAGES - Ramazonov , Shohruh Nusratillo o‘g‘li (Educational Research in Universal Sciences, 2023)
Nowadays there are so many languages in the world, place of the English language occupies an unequal place in the world. I see English as the most global language after my own personal thoughts and a lot of research. we can see that today English is one of the leading languages in the world, it has its own place in each country and it should be noted that it has become the main language for children in schools and they also teach English in kindergartens